High-load positive pole piece, preparation method and high-specific-energy battery

By combining the proportion of small and large-particle polycrystalline ternary materials in the positive electrode sheet, a high-load positive electrode sheet with tortually gradient distribution is prepared, which solves the problem of concentration difference polarization caused by the long lithium ion transmission path, and improves the battery energy density and Performance, and the use of heating slurry and double-layer coating die heads prevent electrode cracking and interface internal resistance.

CN119297199AActive Publication Date: 2025-01-10龙子湖新能源实验室 +2

Patent Information

Application Number
CN202411655693.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-10
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

High load positive electrode sheets lead to long lithium ion transmission paths, resulting in different concentration polarization, affecting the performance of battery energy density, and thick electrodes are prone to cracking during coating, affecting performance.

Method used

By adjusting the proportion of small-particle single crystal and large-particle polycrystalline ternary materials in the first and second electrode layers of the positive electrode sheet, a high-load positive electrode sheet with tortually gradient distribution is prepared to realize the rapid electrolyte diffusion channel and the lithium ion diffusion channel. Reduce concentration polarization, and reduce solvent use by heating the slurry to prevent cracking. At the same time, use a double-layer coating die head for integrated preparation to reduce interface internal resistance.

Benefits of technology

The energy density of the battery is improved, the positive electrode capacity is fully utilized, the internal resistance of the electrode chip is reduced, the battery performance is improved, and the gram capacity and energy density of the battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297199A_ABST
    Figure CN119297199A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and relates to a high-load positive pole piece, a preparation method and a high-specific-energy battery. The positive pole piece is an electrode of a double-layer structure and comprises a current collector, a first electrode layer and a second electrode layer, wherein the first electrode layer and the second electrode layer are far away from the current collector. The specific gravity of the active substance small-particle single crystal ternary material of the first electrode layer is smaller than that of the large-particle polycrystalline ternary material, and the specific gravity of the active substance small-particle single crystal ternary material of the second electrode layer is larger than that of the large-particle polycrystalline ternary material. According to the dual-structure electrode plate, Li < + > migration paths are distributed in a tortuous gradient mode, large and small particles have a synergistic effect, a rapid electrolyte diffusion channel and a rapid lithium ion diffusion channel are achieved, the first electrode layer serves as a rapid transmission layer, the second electrode layer serves as a reaction balance layer, the concentration polarization problem in a thick electrode is effectively solved, the positive electrode capacity can be brought into play, and the service life of the electrode plate is prolonged. The battery energy density is improved. Meanwhile, the prepared positive electrode slurry is heated, high solid content is achieved, the use amount of a solvent is reduced, cracking of a high-load pole piece during coating is prevented, simultaneous coating and integrated preparation of the first electrode layer and the second electrode layer are achieved through the double-layer coating die head, and the interface internal resistance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a positive electrode sheet and a preparation method thereof. Background Art

[0002] High specific energy batteries can store more energy in the same volume or weight. With the popularization of new energy vehicles and the demand for long driving range, there is an urgent need to improve the density of power batteries. In order to increase the energy density of lithium-ion batteries, high-capacity positive and negative electrode materials are generally used and the proportion of battery auxiliary materials is reduced to increase the battery energy density. Since the gram capacity of the negative electrode material is much greater than that of the positive electrode, the main reason restricting the energy density of lithium batteries is the positive electrode. In order to reduce the proportion of battery auxiliary materials, it is necessary to develop high-load positive electrode plates, but the thickness of high-load positive electrode plates is large, and the lithium ion transmission path is long, resulting in large concentration difference polarization on the vertical axis, and the battery capacity is not easy to play out. Secondly, thick electrodes are prone to cracking during the slurry coating process, resulting in an uneven surface of the electrode plate, affecting performance.

[0003] Patent CN109560249A discloses a double-layer structure positive electrode sheet, which adopts a double-layer pore structure with gradually increasing porosity in the positive electrode active unit, that is, the porosity of the second electrode material layer is greater than the porosity of the first electrode material layer, which improves the wettability of the electrolyte in the positive electrode material, the effective diffusion coefficient of lithium ions and the utilization rate of the positive electrode active material, thereby improving the actual gram capacity of the positive electrode material. This invention only increases the electrolyte wettability by regulating the porosity and cannot solve the problem of concentration difference polarization caused by the long migration path of ions in high-load thick electrodes.

[0004] Patent CN111640912 A discloses a method for preparing a positive electrode sheet, wherein the positive electrode active material comprises at least two lithium nickel cobalt manganese oxides LiNi with different morphologies and average particle sizes D50. x Co y Mn 1-x-y O2, by adjusting the ratio of primary single crystal particles and secondary polycrystalline particles and the nickel content, the positive electrode plate can have good thermal stability and excellent kinetic performance, and the lithium-ion secondary battery based on the positive electrode plate can have the characteristics of long cycle at both room temperature and high temperature. This invention controls the size of single crystal and polycrystalline materials and coats a single-layer uniform structure electrode. The electrode plate does not have a tortuous gradient distribution and cannot solve the problem of high-load thick electrodes.

[0005] Patent CN118630149A discloses a method for preparing a high energy density pole piece. The invention coats a polymer film on the surface of a conductive layer to obtain a lightweight current collector; uses a lightweight current collector to coat an active material to prepare a high energy density pole piece; the difference from the traditional current collector is that a lightweight, highly conductive carbon material is used as a lightweight conductive material, and its weight reduction is more obvious. However, it is very limited in reducing the weight of the auxiliary material current collector to increase the battery energy density, and it does not explain the problem of large battery internal resistance caused by high-load electrodes.

[0006] Patent CN118352468A discloses a method for preparing a high surface load electrode. The invention is to achieve high active material utilization of high surface load electrodes by regulating the composition of the electrode coating and the molding process. The uniformly mixed active material, conductive agent, electrolyte and part of the photocuring initiator are formed into a coating on the current collector by in-situ curing. The electrolyte contains a polymerizable monomer, which is polymerized under the action of ultraviolet light, visible light or heat to form a macromolecular network that can improve the binding force between the active material particles by physical interlocking, thereby improving the structural integrity of the electrode and helping to increase the surface capacity of the electrode. Summary of the invention

[0007] In view of the problems existing in high-load positive electrode sheets, the present invention proposes a high-load positive electrode sheet and a preparation method, and a high-energy-density battery. By adjusting the ratio of small-particle single crystals and large-particle polycrystalline ternary materials in the first and second electrode layers of the positive electrode sheet, a high-load positive electrode sheet with a tortuous gradient distribution is prepared, which realizes a fast electrolyte diffusion channel and a lithium ion diffusion channel, effectively alleviates the concentration polarization problem in the thick electrode, helps to exert the positive electrode capacity, and improves the battery energy density. At the same time, high compaction of the electrode sheet can be achieved, and the volume energy density can be improved. At the same time, the prepared positive electrode slurry is heated to achieve high solid content, reduce the amount of solvent used, and prevent cracking during the coating of the high-load electrode sheet. The double-layer coating die head realizes the simultaneous coating of the first and second electrode layers, integrated preparation, and reduced interface internal resistance.

[0008] In order to achieve the above object, the technical solution of the present invention is achieved as follows: A high-load positive electrode plate, the positive electrode plate comprising a current collector and a positive electrode layer, the positive electrode layer comprising a first electrode layer and a second electrode layer along a direction away from the current collector; the positive electrode layer contains an active substance, a conductive agent and a binder; the active substance comprises a single crystal ternary positive electrode material and a polycrystalline ternary positive electrode material, the particle size of the single crystal ternary positive electrode material in the active substance is smaller than that of the polycrystalline ternary positive electrode material; the specific gravity of the single crystal ternary positive electrode material in the first electrode layer is smaller than that of the polycrystalline ternary positive electrode material, and the specific gravity of the single crystal ternary positive electrode material in the second electrode layer is greater than that of the polycrystalline ternary positive electrode material.

[0009] Preferably, the mass ratio of the polycrystalline ternary cathode material to the single-crystalline ternary cathode material in the first electrode layer is (2~9):1; the mass ratio of the single-crystalline ternary cathode material to the polycrystalline ternary cathode material in the second electrode layer is (2~9):1.

[0010] Preferably, the mass ratio of the active material, the conductive agent, and the binder is (92~98):(1.5~4):(0.5~4).

[0011] Preferably, the ternary cathode material is LiNi x Co y Mn 1−x−y O2, where 0 < x < 1, 0 < y < 1 - x; preferably 0.50 < x < 1, 0 < y < 1 - x; more preferably 0.7 < x < 1, 0 < y < 1 - x; even more preferably 0.8 ≤ x < 1, 0 < y < 1 - x.

[0012] Preferably, the D 50 particle size of the single-crystalline ternary cathode material is 1~6 μm; the D 50 particle size of the polycrystalline ternary cathode material is 10~20 μm.

[0013] Preferably, the conductive agent is any one or a combination of several of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fiber; the binder is any one or a combination of several of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, and polyethylene oxide.

[0014] Preferably, the coating surface density of the first electrode layer is 20~25 mg / cm 2 ; the coating surface density of the second electrolyte layer is 15~20 mg / cm 2 .

[0015] Preferably, the method for preparing the high-loading positive electrode sheet includes the following steps: (1) Add the active material, the conductive agent, and the binder to a solvent and heat and homogenize to prepare a first electrode layer slurry and a second electrode layer slurry respectively; (2) Coat the first electrode layer slurry and the second electrode layer slurry in step (1) on the first electrode layer and the second electrode layer respectively.

[0016] Preferably, the temperature of the heating and homogenizing in step (1) is 30~50 °C; the solid content of the slurry is 75~85 wt%; the viscosity is 5000~8000 mPa·s; the solvent is N-methylpyrrolidone.

[0017] Preferably, in step (2), a double-layer coating die head is used to coat the first electrode layer and the second electrode layer simultaneously; A high-energy-density battery, wherein the positive electrode plate of the battery is the high-load positive electrode plate, and the negative electrode plate is a silicon-based negative electrode plate or a lithium metal plate; the positive and negative electrode plates are stacked, packaged, injected, formed, and divided into different volumes to prepare a high-energy-density soft-pack battery.

[0018] The present invention has the following beneficial effects: 1. The present invention proposes a high-load positive electrode sheet and a preparation method, which realizes the tortuosity gradient distribution of the high-load positive electrode sheet by adjusting the ratio of small-particle single crystal and large-particle polycrystalline ternary materials in the first and second electrode layers of the positive electrode sheet. The low tortuosity of the first electrode layer realizes Li + Fast transport; large particle active materials with high tortuosity in the second electrode layer at low Li + Deep delithiation can be achieved at a certain concentration and reaction balance can be achieved, thereby solving the concentration polarization problem of high-load electrodes during charging and discharging, making full use of the capacity of the positive electrode sheet and improving the battery energy density.

[0019] 2. The second electrode layer of the present invention is mainly composed of small-particle single-crystal ternary materials, which realizes high compaction of the electrode sheet. High compaction of the electrode sheet reduces the ion migration path, reduces the internal resistance of the electrode sheet, and improves battery performance. The polycrystalline and single-crystal ternary material of the present invention are compounded in large and small particles to achieve particle synergy, reduce the volume expansion of the electrode sheet during charging and discharging, and improve the battery capacity.

[0020] 3. The present invention adopts a heating homogenization method to achieve high solid content slurry preparation, reduce the amount of organic solvent used, and prevent cracking during high load electrode coating. The first and second electrode layers are coated at the same time, integrated preparation, and reduce interface internal resistance.

[0021] 4. The positive electrode sheet prepared by the method of the present invention is applied to high specific energy batteries, and its single-sided coating density can reach 40 mg / cm 2 , achieving the preparation of high active material loading and thick electrode sheets, while achieving the effect of high battery energy density. The prepared battery energy density can reach up to 360Wh / Kg, which is significantly higher than the comparative data (290Wh / Kg). BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 It is a schematic diagram of the structure of the positive electrode plate of the present invention.

[0024] Figure 21 is the discharge curve of the soft-pack battery of Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The ternary positive electrode materials used in the embodiments of the present invention were purchased from Beijing Dangsheng Materials Technology Co., Ltd.

[0027] Example 1 The positive electrode sheet and the soft-pack battery of this embodiment are prepared by the following steps: (1) The single crystal ternary positive electrode material in the active material is LiNi 0.93 Co 0.05 Mn 0.02 O2 and polycrystalline ternary cathode materials are LiNi 0.9 Co 0.06 Mn 0.04 O2; D of single crystal and polycrystalline materials 50 The particle sizes are 4μm and 13μm respectively; the active material, conductive carbon black and binder polyvinylidene fluoride are mixed in a ratio of 97:3:1 and heated at 35°C to prepare the first and second layers of positive electrode slurries respectively, wherein the mass ratios of single crystals and polycrystals of the first and second layers of active materials are 1:9 and 9:1; the solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 7000mPa.s and the solid content to 78%.

[0028] (2) The slurry prepared in step (1) is coated with a double-layer coating die at a first electrode layer density of 20 mg / cm 2 The second electrode layer density is 15 mg / cm 2 The coating is carried out at the same time, and the structure of the obtained positive electrode sheet is as follows Figure 1 shown.

[0029] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0030] Example 2 The positive electrode sheet and the soft-pack battery of this embodiment are prepared by the following steps: (1) Single crystal ternary material LiNi in active material 0.93 Co 0.05Mn 0.02 O2 and polycrystalline ternary material LiNi 0.9 Co 0.06 Mn 0.04 O2, D of single crystal and polycrystalline materials 50 The particle sizes are 3μm and 15μm respectively; the active material, conductive carbon black, and binder polyvinylidene fluoride are mixed in a ratio of 96:2.5:1.5 and heated at 40°C to prepare the first and second layers of positive electrode slurries, wherein the mass ratios of single crystals and polycrystals of the first and second layers of active materials are 1:4 and 4:1; the solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 6000mPa.s and the solid content to 80%.

[0031] (2) The slurry prepared in step (1) is coated with a double-layer coating die according to the first electrode layer density of 22 mg / cm 2 The second electrode layer density is 16 mg / cm 2 The coating is carried out simultaneously.

[0032] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0033] Example 3 The positive electrode sheet and the soft-pack battery of this embodiment are prepared by the following steps: (1) The single crystal ternary material in the active material is LiNi 0.93 Co 0.05 Mn 0.02 O2, polycrystalline ternary material is LiNi 0.9 Co 0.06 Mn 0.04 O2; D of single crystal and polycrystalline materials 50 The particle sizes are 2μm and 14μm respectively; the active material, conductive carbon black and binder polyvinylidene fluoride are mixed in a ratio of 97.5:1.5:1 and heated at 45°C to prepare the first and second layers of positive electrode slurries respectively, wherein the mass ratios of single crystals and polycrystals of the first and second layers of active materials are 3:7 and 7:3 respectively; the solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 5500mPa.s and the solid content to 82%.

[0034] (2) The slurry prepared in step (1) is coated with a double-layer coating die according to the first electrode layer density of 22 mg / cm 2 The second electrode layer density is 18 mg / cm 2 The coating is carried out simultaneously.

[0035] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0036] Example 4 The positive electrode sheet and the soft-pack battery of this embodiment are prepared by the following steps: (1) The single crystal ternary positive electrode material in the active material is LiNi 0.8 Co 0.1 Mn 0.1 O2 and polycrystalline ternary cathode materials are LiNi 0.92 Co 0.04 Mn 0.04 O2; D of single crystal and polycrystalline materials 50 The particle sizes are 4μm and 13μm respectively; the active material, conductive agent (Ketjen black and carbon nanotubes in a mass ratio of 1:1) and binder (polyvinylidene fluoride and polyethylene oxide in a mass ratio of 1:1) are mixed in a ratio of 98:1.5:0.5 and heated at 35°C to prepare the first and second layers of positive electrode slurries, wherein the mass ratios of single crystals and polycrystals of the first and second layers of active materials are 1:2 and 2:1; the solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 6000mPa.s and the solid content to 83%.

[0037] (2) The slurry prepared in step (1) is coated with a double-layer coating die at a first electrode layer density of 20 mg / cm 2 The second electrode layer density is 15 mg / cm 2 The coating is carried out simultaneously.

[0038] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0039] Example 5 The positive electrode sheet and the soft-pack battery of this embodiment are prepared by the following steps: (1) The single crystal ternary positive electrode material in the active material is LiNi 0.93 Co 0.05 Mn 0.02 O2 and polycrystalline ternary cathode materials are LiNi 0.9 Co 0.06 Mn 0.04 O2; D of single crystal and polycrystalline materials 50The particle sizes are 1μm and 10μm respectively; the active material, conductive agent (acetylene black and carbon fiber in a mass ratio of 7:3) and binder polyethylene oxide are mixed in a ratio of 92:4:4 and heated at 30°C to prepare the first and second layers of positive electrode slurries respectively, wherein the mass ratios of single crystals and polycrystals of the first and second layers of active materials are 1:9 and 9:1; the solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 5000mPa.s and the solid content to 75%.

[0040] (2) The slurry prepared in step (1) is coated with a double-layer coating die at a first electrode layer density of 20 mg / cm 2 The second electrode layer density is 15 mg / cm 2 The coating is carried out simultaneously.

[0041] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0042] Example 6 The positive electrode sheet and the soft-pack battery of this embodiment are prepared by the following steps: (1) The single crystal ternary positive electrode material in the active material is LiNi 0.93 Co 0.05 Mn 0.02 O2 and polycrystalline ternary cathode materials are LiNi 0.9 Co 0.06 Mn 0.04 O2; D of single crystal and polycrystalline materials 50 The particle sizes are 6μm and 20μm respectively; the active material, the conductive agent (graphene and Ketjen black in a mass ratio of 3:7) and the binder sodium carboxymethyl cellulose are mixed in a ratio of 97:3:1 and heated to 50°C to prepare the first and second layers of positive electrode slurries respectively, wherein the mass ratios of single crystals and polycrystalline active materials in the first and second layers are 1:9 and 9:1; the solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 8000mPa.s and the solid content to 85%.

[0043] (2) The slurry prepared in step (1) is coated with a double-layer coating die at a first electrode layer density of 25 mg / cm 2 The second electrode layer density is 20 mg / cm 2 The coating is carried out simultaneously.

[0044] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0045] Comparative Example 1 The positive electrode sheet and the soft pack battery of this comparative example are prepared by the following steps: (1) The active material single crystal ternary material LiNi 0.93 Co 0.05 Mn 0.02 O2 and polycrystalline ternary material LiNi 0.9 Co 0.06 Mn 0.04 O2, conductive carbon black, and binder polyvinylidene fluoride were mixed in a ratio of 97.5:1.5:1 and heated at 45°C to prepare the slurry. The mass ratio of active material single crystal to polycrystalline was 1:1; the D 50 The particle sizes are 2 μm and 14 μm respectively; solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 6500 mPa.s and the solid content to 80%.

[0046] (2) The slurry prepared in step (1) was prepared with a surface density of 40 mg / cm 2 Apply a single layer.

[0047] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0048] Comparative Example 2 The positive electrode sheet and the soft pack battery of this comparative example are prepared by the following steps: (1) The active material single crystal ternary material LiNi 0.93 Co 0.05 Mn 0.02 O2, conductive carbon black, and binder polyvinylidene fluoride were mixed in a ratio of 96:2.5:1.5 and heated at 45°C to prepare the positive electrode slurry. 50 The particle sizes are 2 μm respectively; solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 8000 mPa.s and the solid content to 75%.

[0049] (2) The slurry prepared in step (1) was prepared with a surface density of 40 mg / cm 2 Apply a single layer.

[0050] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0051] Comparative Example 3 The positive electrode sheet and the soft pack battery of this comparative example are prepared by the following steps: (1) The active material polycrystalline ternary material LiNi 0.9 Co 0.06 Mn 0.04 O2, conductive carbon black, and binder polyvinylidene fluoride were mixed in a ratio of 97.5:1.5:1 and heated at 45°C to prepare the slurry. 50 The particle sizes are 14 μm respectively; solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 5000 mPa.s and the solid content to 85%.

[0052] (2) The slurry prepared in step (1) was prepared with a surface density of 40 mg / cm 2 Apply a single layer.

[0053] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0054] Comparative Example 4 The positive electrode sheet and the soft pack battery of this comparative example are prepared by the following steps: (1) The single crystal ternary material in the active material is LiNi 0.93 Co 0.05 Mn 0.02 O2, polycrystalline ternary material is LiNi 0.9 Co 0.06 Mn 0.04 O2; D of single crystal and polycrystalline materials 50 The particle sizes are 2μm and 14μm respectively; the active material, conductive carbon black and binder polyvinylidene fluoride are mixed in a ratio of 97.5:1.5:1 and heated at 45°C to prepare the first and second layers of positive electrode slurries respectively, wherein the mass ratios of single crystals and polycrystals of the first and second layers of active materials are 7:3 and 3:7; the solvent N-methylpyrrolidone is added to adjust the slurry viscosity to 6000mPa.s and the solid content to 83%.

[0055] (2) The slurry prepared in step (1) is coated with a double-layer coating die according to the first electrode layer density of 22 mg / cm 2 The second electrode layer density is 18 mg / cm 2 The coating is carried out simultaneously.

[0056] (3) Using the high-load positive electrode sheet prepared as described above, the negative electrode sheet adopts a silicon oxide 550 negative electrode sheet; stacking (15 layers of positive electrode, 16 layers of negative electrode), packaging, liquid injection (liquid injection coefficient 2.0g / Ah), formation, capacity division and other processes are carried out to prepare a 40Ah soft-pack battery.

[0057] The batteries prepared in Examples 1-6 and Comparative Examples 1-4 are different except for the positive electrode layer, and the negative electrode and packaging of the batteries are made using the same process. The electrode parameters and soft-pack battery data of Examples 1-3 and Comparative Examples 1-4 are shown in Table 1: Table 1 Soft-pack battery data of Examples 1-3 and Comparative Examples 1-4 The difference between Comparative Example 1-3 and Example 1-3 is that Comparative Example 1-3 uses a single-layer positive electrode, and the rest of the battery preparation process is the same. According to the data in Table 1, the electrode and battery of Example 3 prepared by the method of the present invention show higher gram capacity and battery energy density (such as Figure 2 As shown), this is because the present invention achieves a tortuosity gradient distribution of a high-load positive electrode sheet by adjusting the ratio of small-particle single crystal and large-particle polycrystalline ternary materials in the first and second electrode layers of the positive electrode sheet. The first electrode layer has a low tortuosity to achieve rapid transmission, and the second electrode layer can achieve reaction balance with high tortuosity, thereby solving the concentration polarization problem of high-load electrodes in charging and discharging, making full use of the capacity of the positive electrode sheet, and improving the energy density of the battery. The second electrode layer is mainly composed of small-particle single crystal ternary materials to achieve high compaction of the electrode sheet. The high compaction electrode sheet reduces the ion migration path, reduces the internal resistance of the electrode sheet, and improves the battery performance. The large and small particles of polycrystalline and single crystal ternary materials are compounded to achieve particle synergy, reduce the volume expansion of the electrode sheet during charging and discharging, and improve the battery capacity. Comparative Examples 2 and Comparative Examples 3 use pure single crystal and pure polycrystalline positive electrode active materials, respectively, and are coated as single-layer structure positive electrodes. The positive electrode sheets do not have a tortuosity gradient structure, so the prepared battery energy density is low and the positive electrode plays a low gram capacity. Comparative Example 4 has an opposite ratio of single crystal and polycrystalline in the first and second electrode layers compared to Example 3. The ion migration path in the second electrode layer is long, and Li + The migration rate is lower than the interface reaction rate, resulting in a large concentration polarization. The ion migration path of the first electrode layer is short and cannot play a role in reaction equilibrium, so its electrode capacity is relatively low.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-load positive electrode plate, characterized in that: The positive electrode sheet includes a current collector and a positive electrode layer, the positive electrode layer includes a first electrode layer and a second electrode layer along a direction away from the current collector; the positive electrode layer contains an active substance, a conductive agent and a binder; the active substance includes a single crystal ternary positive electrode material and a polycrystalline ternary positive electrode material, and the particle size of the single crystal ternary positive electrode material in the active substance is smaller than that of the polycrystalline ternary positive electrode material; the specific gravity of the single crystal ternary positive electrode material in the first electrode layer is smaller than that of the polycrystalline ternary positive electrode material, and the specific gravity of the single crystal ternary positive electrode material in the second electrode layer is greater than that of the polycrystalline ternary positive electrode material.

2. The high-load positive electrode plate according to claim 1, characterized in that: The mass ratio of the polycrystalline ternary positive electrode material to the single crystal ternary positive electrode material of the first electrode layer is (2-9):1; the mass ratio of the single crystal ternary positive electrode material to the polycrystalline ternary positive electrode material of the second electrode layer is (2-9):

1.

3. The high-load positive electrode plate according to claim 1, characterized in that: The D of the single crystal ternary cathode material 50 Particle size is 1~6μm; polycrystalline ternary cathode material D 50 The particle size is 10~20μm.

4. The high-load positive electrode sheet according to any one of claims 1 to 3, characterized in that: The mass ratio of the active material, the conductive agent and the binder is (92-98):(1.5-4):(0.5-4).

5. The high-load positive electrode plate according to claim 4, characterized in that: The ternary positive electrode material is LiNi x Co y Mn 1−x−y O2, where 0 <x<1,0<y<1-x。 6. The high-load positive electrode plate according to claim 4, characterized in that: The conductive agent is any one or a combination of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fibers; The binder is any one or a combination of polyvinylidene fluoride, sodium hydroxymethyl cellulose, sodium alginate and polyethylene oxide.

7. The high-load positive electrode plate according to claim 4, characterized in that: The coating surface density of the first electrode layer is 20-25 mg / cm 2 ; The coating density of the second electrode layer is 15~20mg / cm 2 .

8. The method for preparing a high-load positive electrode sheet according to any one of claims 1 to 7, characterized in that: The steps include: (1) adding an active material, a conductive agent, and a binder into a solvent and heating and homogenizing the mixture to prepare a first electrode layer slurry and a second electrode layer slurry respectively; (2) The first electrode layer slurry and the second electrode layer slurry prepared in step (1) are respectively coated with the first electrode layer and the second electrode layer.

9. The method for preparing a high-load positive electrode sheet according to claim 8, characterized in that: The temperature of heating the slurry in step (1) is 30-50° C.; the solid content of the slurry is 75-85wt%; the viscosity is 5000-8000 mPa.s; and the solvent is N-methylpyrrolidone.

10. A high specific energy battery, characterized in that: The positive electrode plate of the battery is the high-load positive electrode plate as described in any one of claims 1 to 7, and the negative electrode plate is a silicon-based negative electrode plate or a lithium metal plate; the positive electrode plates and the negative electrode plates are stacked, packaged, injected, formed, and divided into different volumes to prepare a high-energy-density soft-pack battery.

Citation Information

Patent Citations

  • Positive electrode sheet capable of discharging at high rate, and lithium ion battery comprising positive electrode sheet

    CN112151794A

  • Preparation method of composite electrode pole piece, composite electrode pole piece and lithium ion battery

    CN114597351A

  • Positive pole piece, positive pole piece preparation method, lithium ion battery and EVTOL

    CN118198264A

  • Positive electrode plate and lithium ion battery

    US20200006767A1

Cited By

  • Battery cell, battery, and electric device

    WO2026200187A1